Kesantunan Bahasa Peserta Diskusi ILC Tema “Tahun Politik Makin Panas: Tampang Boyolali vs Sontoloyo” - Sabrina, Reno Mardhatillah; Satriawan, Nofri (Orasi: Jurnal Ilmu Politik dan Sosial, 2025)
This study aims to describe the politeness of the discussion participants in the Indonesia Lawyers Club program theme "The Year of Politics is Increasingly Hot: The Look of Boyolali vs. Sontoloyo" on November 6 2018. Data analysis and discussion in this study rests on Leech's theory which describes six maxims (provisions and teachings ) namely: (1) wisdom maxim (tact maxim), (2) generosity (generosity maxim), (3) maxim maxim (approbation maxim), (4) humility (mode maxim), (5) agreement maxim (agreement maxim ), and (6) sympathy maxim. This research method is a qualitative descriptive method by recording recorded data, analyzing all data obtained, identifying data and checking the validity of the data, and concluding the results of research on politeness in ILC events. Based on the data collected, it was found that there were many forms of violations of politeness from harsh words issued and high notes that were widely used by ILC discussion participants.